Exploring Climate Emotions in Canada’s Provincial North - Galway, Lindsay P.; Beery, Thomas (Frontiers in Psychology, 2022)
The mental and emotional dimensions of climate change are increasingly concerning as extreme events become more frequent and severe, ecosystem destruction advances, and people become more aware of climate impacts and injustices. Research on climate emotions has rapidly advanced over the last decade with growing evidence illustrating that climate emotions can impact health, shape climate action, and ought to be considered in climate change communication, education, and engagement. This paper explores, describes, and discusses climate emotions in the context of Canada’s Provincial North: a vast region characterized by a vulnerability to climate change, remoteness, political marginalization, diverse Indigenous populations, and economies/livelihoods tied to resource extraction. Using postal survey data collected in two Provincial North communities (Thunder Bay, Ontario, and Prince George, British Columbia; N = 627), we aim to (1) describe climate emotions experienced in the context of Canada’s Provincial North, including relationships among specific emotions; and (2) examine if socio-demographic variables (gender, age, and parenthood) show a relationship with climate emotions. Results show high levels of emotional response to climate change overall, with worry and frustration as those emotions reported by the highest percentage of participants. We also find significant difference in climate emotions between men and women. A methodological result was noted in the usefulness of the Climate Emotion Scale (CES), which showed high reliability and high inter-item correlation. A notable limitation of our data is its’ underrepresentation of Indigenous peoples. The findings contribute to a greater understanding of climate emotions with relevance to similar settings characterized by marginalization, vulnerability to climate change, urban islands within vast rural and remote landscapes, and economies and social identities tied to resource extraction. We discuss our findings in relation to the literature and outline future research directions and implications.